PERAN LINGKUNGAN INTERNAL DAN EKSTERNAL SEKOLAH DALAM KEBERHASILAN IMPLEMENTASI KEBIJAKAN PENDIDIKAN - Umi Iriani; Rustam Ali; Muhammad Syaifudin (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study analyzes the role of internal and external school environments in determining the success of education policy implementation. Education policies, although well formulated, often face challenges during implementation due to variations in school capacity, organizational culture, and socio-political contexts. Using a qualitative library research method, this study examines various scholarly sources, journals, books, and academic documents that discuss policy implementation and environmental factors influencing schools. The results show that internal factors including communication, availability of resources, implementers' disposition, bureaucratic structure, and school culture serve as the foundational elements that shape schools' readiness and ability to implement policies effectively. Meanwhile, external factors such as regulatory support, political stability, socioeconomic conditions, and parental or community participation significantly influence the success of implementation by providing contextual support beyond the school. The study also highlights that the interaction between internal and external environments forms a holistic system in which imbalance in either dimension may hinder policy outcomes. The conclusion emphasizes that alignment between internal capacity and external support is essential for ensuring that education policies are executed optimally and achieve their intended goals.Keywords:internal environment, external environment, policy implementation, school management, education policy